'Text-work' in Research Ethics Review: The significance of documents in and beyond committee meetings. (17th November 2018) - Morton, Julie
ABSTRACT: This article analyzes how a formal text (the Ethics Review Form) available at National Health Service Research Ethics Committees (NHSRECs) in the United Kingdom was used in meetings. Derived from the work of Dorothy Smith on incorporating texts into institutional ethnography (IE), it proposes the concept of "text work" as a way into understanding more about decision-making in ethics review and describes the extent to which this formal text shaped and influenced review work. The research study used observations of committee meetings, field-notes and interviews to produce an ethnographic mapping of Research Ethics Committees' (RECs) work. This article draws on one aspect of the research which was the process of isolating a particular, ubiquitous text and analyzing how it worked and was worked on in the meetings. The analysis contributes to contemporary discussion offering an alternative to ongoing debates about idealized ways of conducting ethics review. Finally, some tentative suggestions are made about improving training, based on and starting from the work which reviewers undertake.